Inteligência Artificial no Ensino Superior: promovendo práticas de ensino voltadas à sustentabilidade com o sistema GrowAIDE - Saldanha, Marros Silva (Universidade do Vale do Rio dos Sinos, 2025)
The integration of sustainability-oriented teaching practices in higher education is essential to train professionals who are aware of current socio-environmental challenges. This dissertation investigates how the GrowAIDE system (available at: https://www.growaide.app/), using artificial intelligence, contributes to sustainable education in a private HEI in Rio Grande do Sul through the analysis of contextual data and the generation of personalized strategies to integrate sustainability into business projects developed in the educational field. The general objective of this research is to evaluate how the GrowAIDE system, based on artificial intelligence, can be implemented in a Higher Education Institution to promote education integrated with teaching practices focused on sustainability. This analysis will be guided by the following specific objectives: to develop a teaching resource with the system, to evaluate perceptions of its usability and to verify its pedagogical adaptation. This is an exploratory research with a mixed approach, which involved four experienced professors in sustainability and used Likert scale questionnaires and semi-structured interviews. The research evaluated the GrowAIDE system as a teaching resource. The quantitative data from the questionnaires provided an initial overview of the perceptions, while the qualitative data from the interviews were analyzed using Critical Discourse Analysis (CDA) (Fairclough, 1995) to gain an in-depth understanding of the participants' constructions of meaning. As a result of this research, it can be concluded that GrowAIDE can be used as a strategic tool for HEIs to promote concepts and teaching practices related to sustainability. However, it was also found that the system requires improvements in accessibility and a more intuitive interface for personalizing the information entered in the project registration, thus optimizing the analysis performed by artificial intelligence. This work, developed within the scope of a Professional Master's Degree, resulted in the design, development and evaluation of the GrowAIDE system, a technological product applied to higher education to promote practices aligned with sustainability.
Keywords: Inteligência artificial; Ensino superior; Sustentabilidade; Práticas de ensino; Artificial intelligence; Higher education; Sustainability; Teaching practices; ACCNPQ::Ciências Humanas::Educação